2018
DOI: 10.1111/age.12695
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for squamous cell carcinoma of the nictitating membrane parallels that of the limbus in Haflinger horses

Abstract: Squamous cell carcinoma (SCC) is the most common cancer affecting the equine eye, with a higher incidence documented in Haflinger horses. Recently, a missense variant in the gene damage specific DNA binding protein 2 (DDB2, p.Thr338Met) on ECA12 was identified as a risk factor for the development of limbal SCC in Haflinger horses. SCC also occurs on the nictitating membrane; therefore, investigating the role of this missense variant in nictitating membrane SCC is warranted. In this study, a common ancestor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…The median age at diagnosis of ocular SCC or carcinoma in situ in this sample was 11 years (range: 5-27 years). The median age at the time of examination of the control group was 15 years (range: [13][14][15][16][17][18][19][20][21][22][23][24][25]. The median age of the affected group was significantly younger than that of the control group (U = 101, P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age at diagnosis of ocular SCC or carcinoma in situ in this sample was 11 years (range: 5-27 years). The median age at the time of examination of the control group was 15 years (range: [13][14][15][16][17][18][19][20][21][22][23][24][25]. The median age of the affected group was significantly younger than that of the control group (U = 101, P = 0.002).…”
Section: Resultsmentioning
confidence: 99%
“…The same study identified the frequency of the variant risk allele in a sample of unphenotyped Belgian horses (0.21) to be comparable to that of the Haflinger breed (0.25); however, the status of the Belgian horses in that study with regard to whether or not they were affected with ocular SCC was unknown . The DDB2 c.1013 C > T , p.Thr338Met variant was also confirmed as a risk factor for third eyelid SCC in the Haflinger breed, with 88% of Haflinger horses with SCC in this location determined to be homozygous for the variant . The DDB2 c.1013 C > T variant allele was most recently described to have a frequency of 0.20 in the Rocky Mountain Horse breed, and an initial ocular SCC‐affected case was found to be homozygous T for the variant, suggesting the variant may also serve as a risk factor in Rocky Mountain Horses .…”
Section: Introductionmentioning
confidence: 81%
“…[2][3][4] A mutation in the damage-specific DNA-binding protein 2 (DDB2) has been identified which increases the risk of developing SCC of the limbus and nictitans membrane in horses, specifically in the Haflinger and Belgium breeds. 5,6 A gender predilection has also been proposed with castrated males being overrepresented, 2,7,8 although this is not supported by other studies. This epithelial neoplasm in horses has been described originating from the cornea, limbus, conjunctiva, nictitans membrane, and eyelid.…”
Section: Introductionmentioning
confidence: 92%
“…Draught horses, the Haflinger breed, and Appaloosa horses have been shown to be predisposed to SCC development . A mutation in the damage‐specific DNA‐binding protein 2 ( DDB2 ) has been identified which increases the risk of developing SCC of the limbus and nictitans membrane in horses, specifically in the Haflinger and Belgium breeds . A gender predilection has also been proposed with castrated males being overrepresented, although this is not supported by other studies.…”
Section: Introductionmentioning
confidence: 98%
“…Homozygosity for the risk factor ( DDB2 c.1013 C > T ; rs1139682898) was found to be strongly associated with limbal SCC in the Haflinger breed ( P = 3.41 × 10 −10 ) and explained 77% of included cases. The DDB2 risk factor was also identified to be strongly associated with SCC of the third eyelid in Haflingers ( P = 4.13 × 10 −14 ), explaining an even greater number of those cases, specifically 88% . Subsequently, a strong association between the DDB2 variant and all forms of ocular SCC in Belgian horses has been demonstrated (Knickelbein et al, under review).…”
Section: Introductionmentioning
confidence: 96%